War in the Hebrew Bible : a study in the ethics of violence - Niditch, Susan (New York : Oxford University Press, 1993)
Texts about war pervade the Hebrew Bible, raising challenging questions in religious and political ethics. The war passages that readers find most disquieting are those in which God demands the total annihilation of the enemy without regard to gender, age, or military status. The ideology of the ""ban, "" however, is only one among a range of attitudes towards war preserved in the ancient Israelite literary tradition. Applying insights from anthropology, comparative literature, and feminist studies, Niditch considers a wide spectrum of war ideologies in the Hebrew Bible, seeking in each case to
COVER PAGE; TITLE PAGE; COPYRIGHT PAGE; DEDICATION; ACKNOWLEDGMENTS; CONTENTS; ABBREVIATIONS; Introduction; A Chain of Tradition: The Terrible Burden; Tracing Roots, Assigning Blame; Previous Work; Methodological Challenges: History and Authors; Cross-Disciplinary Approaches to War; Types of War and Social Organization: Defining Society, the Self, and the Other; Roots of War: Justifying Killing, Underlying Causes; War, Guilt, and Scapegoats; Just Wars and Crusades; 1: The Ban as God's Portion; The Ban; The Ban in a Sacrificial Context; War, Death, and Sacrificial Feasts. Roots of Discomfort: Interesting AmbivalencesViolent Death of One's Own versus Killing the "Other": Martyrdom and the Ban; Origins and Actualization; How and for Whom Is the Ban as Sacrifice Meaningful?; Self-conceptions Implied by Images of the Ban as Sacrifice; Israelite Origins and the Ban as Sacrifice; Ideology, Actuality, and Chronology; 2: The Ban as God's Justice; Jericho and Achan; Saul and Agag; Covenantal Framework for the Ban as God's Justice; Neatening Up War Ideologies: Deuteronomy 20; The Ban Gone Awry: Critique?; Leaders Who Employ the Ban?; History and the Ban as God's Justice. Guilt, Killing, Kin, Purity: The Ban as Sacrifice versus the Ban as God's Justice3: The Priestly Ideology of War in Numbers; War and Vengeance; Placing under the Ban and Numbers 31: Revealing Differences; A Strongly Hierarchical Vision of War; Women as Chattel, Issues of Purity: Judges 21, Deuteronomy 21, and Numbers 31; War and Purity: Contrast between Ban Texts and Numbers 31; Conclusions; 4: The Bardic Tradition of War; War as Part of a Literary Pattern; "Men of Valor"; Taunts; Taunting and the Battle with Goliath; War as Sport; Codes, Combat, and Kin. Limitations in Non-Bardic Texts: Kin and Non-KinReciprocity of Various Sorts; Dividing the Spoil; Mock-Heroic; Conclusions; 5: The Ideology of Tricksterism; The Rape of Dinah: Genesis 34; The Story; The Ideology: Genesis 34 in a Spectrum; Samson and the Timnites; Jael: Sexuality, Tricksterism, and Violence; Ehud and Eglon: Judges 3: 12-30; Conclusions; A More Respectable Tricksterism; 6: New Perspectives on African-American Violence; An Opening Case: The Critique of Naked Aggression; The Usual Literary Pattern of State-Sponsored War; A Case of Claiming Just Cause. Expedient Wars without Just Cause or CodeEcological Materialism in Earnest and Up-Front; Dead People Cannot Fight (or Tell Secrets); Brutality in War and the Aftermath; Booty in Goods and People; Implicit Critique: The Work of the Chronicler; 7: Toward an Ideology of Nonparticipation; Domination versus Reconciliation; A Critique of War?; Overt Critiques of Warring Behavior in Gen 49 and Amos 1-2; 1 and 2 Chronicles and War; The Chronicler and Crusade; Peace as Victory in War; God Loves the Weak and Controls the War; Miracles
Includes bibliographical references( p. 157-169) and index
Keywords: War -- Biblical teaching; Bible. O.T. -- Criticism, interpretation, etc